SYNTACTIC STRUCTURE AND PRAGMATIC INTERPRETATION OF EMBEDDED QUESTIONS IN MUYANG - Bebey , Théodore (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
The present article tackles the structure and semantics of embedded questions in Muyang. The main question is how this syntactic element is structured and interpreted within a complex and populated map of the clause left periphery exhibited by Muyang language (Bebey, 2015). The article aims to highlight the syntactic and pragmatic characteristics of embedded questions. Data are collected from Muyang native speakers. It uses the cartographic theory and a descriptive-analytical approach. This article demonstrates that the complementizer kado‘that’which expresses illocutionary force cross linguistically co-construes with embedding markers bi (whether) and tamala (if) also analyzed as illocutionary force indicators, a remark that leads to the assumption that there may be a distinct projection of the Embedded-Question Phrase (EmQP). It also reveals that the syntactic configuration of the embedded question (EmQ)’s head is made up of a number of constituents that interpolate between the complementizerkadoor ti‘ that’ and the embedding markersbi ‘whether’ and tamala ‘if’,the selection of which depends on syntactic properties and pragmatic requirements. It provides evidence that contrary to Biloa (2013 and 2019), Bebey (2015) and subsequent works, that Wh-questions cannot be analyzed as types of focusing in Chadic languages. Given the complexity of that position, this article suggests following Jean-Yves Pollock (1989), Rizzi (1997, 2001) and subsequent works that it may split up into distinct maximal projections ranged as follows: ForceP.